Presenting virtually : communicate and connect with online audiences - Sanchez, Patti (California : Duarte Press, 2021)
Communicating to audiences remotely is an essential skill because the future of work is largely happening online. You've got to become a pro at virtual presenting so you can connect with others at a distance. This practical guide lays out a step-by-step process for planning, crafting, and delivering virtual presentations that will hold your audiences' attention and move them to embrace your ideas. Whether you have to give online presentations every day or every once in a while, this book will help you: Master the skill of presenting remotely so you can reach and influence audiences in any location or time zone Communicate ideas to remote audiences with greater clarity, creativity, and impact so your ideas are noticed, understood, and remembered, even when you're not presenting in person Strengthen your personal brand and reputation by showing up with a professional and memorable presence anytime you're presenting remotely.
Introduction -- Context -- Strategy -- Story -- Visuals -- Delivery -- Conclusion -- Appendix.
Includes bibliographical references and index.
Keywords: BUSINESS PRESENTATIONS